Pressure forces on sediment particles in turbulent open-channel flow: a laboratory study. (19th September 2014) - Amir, Mohammad; Nikora, Vladimir I.; Stewart, Mark T.
Abstract: An experimental investigation into the fluctuating pressure acting on sediment particles on the bed of an open-channel flow was carried out in a large laboratory flume for a range of flow depths and bed slopes. The pressure measurements were made using 23 spherical particles instrumented with differential pressure sensors. These measurements were complemented with simultaneous measurements of the velocity field using high-resolution stereoscopic particle image velocimetry. The pressure statistics show that the standard deviations of the drag and lift fluctuations vary from 2.0 to 2.6 and from 2.5 to 3.4 times the wall shear stress, respectively, and are dependent on relative submergence and flow Reynolds number. The skewness is positive for the drag fluctuations and negative for the lift fluctuations. The kurtosis values of both drag and lift fluctuations increase with particle submergence. The two-particle correlation between drag and lift fluctuations is found to be relatively weak compared to the two-point drag–drag and lift–lift correlations. The pressure cross-correlations between particles separated in the longitudinal direction exhibit maxima at certain time delays corresponding to the convection velocities varying from 0.64 to 0.72 times the bulk flow velocity, being very close to the near-bed eddy convection velocities. The temporal autocorrelation of drag fluctuations decays much faster than that for the lift fluctuations; as a result, the temporal scales of lift fluctuations are 3–6 times that of drag fluctuations. The spatial and temporal scales of both drag and lift fluctuations show dependence on flow depth and bed slope. The spectral behaviour of both drag and lift fluctuations is also assessed. A $\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let ≤ =\leqslant \let \ge =\geqslant \let ≥ =\geqslant \def \Pr {Pr}\def \Fr {Fr}\def \Rey {Re}f^{-11/3}$ slope is observed for the spectra of the drag fluctuations over the majority of the frequency range, whereas the lift spectra suggest two scaling ranges, following a $f^{-11/3}$ slope at high frequencies and $f^{-5/3}$ behaviour at lower frequencies.